The Effects of Objective and Subjective Socioeconomic Status on Subjective Well-Being among Rural-to-Urban Migrants in China: The Moderating Role of Subjective Social Mobility - Silin Huang; Jiawei Hou; Ling Sun; Donghui Dou; Xia Liu; Hongchuan Zhang (Frontiers in Psychology, 2017)
Although previous investigations have agreed that Chinese rural-to-urban migrants’ socioeconomic status (SES) increases with their migration, the association between SES and subjective well-being is uncertain. To address this research gap, the present study proposed that the association between objective SES and subjective well-being is mediated by subjective SES. This model was tested with a sample of 432 Chinese rural-to-urban migrants. The results indicate a significant association between objective SES and subjective well-being and a partial mediating effect of subjective SES. Furthermore, subjective social mobility, which is one’s expectation about the possibility to move upward in the social hierarchy, was found to moderate both the direct path from objective SES to subjective well-being and the indirect path from subjective SES to subjective well-being. These findings suggest that Chinese rural-to-urban migrants gained in subjective well-being not only because of direct financial achievement but also because of their perceptions and beliefs about their relative social status.